British Identities before Nationalism : Ethnicity and Nationhood in the Atlantic World, 1600-1800. - Kidd, Colin (Cambridge University Press, 2003)
This offers a comprehensive coverage of ethnic and national identities in the British world in the era which immediately preceded the onset of modern racialist and nationalist thinking. Ranging across the political cultures of England, Scotland, Ireland and revolutionary America, it also considers European influences and comparisons.